Analysis of Santri's critical thinking with Problem Solving approach - Yuliana Trisanti; Hairus Saleh; Fetty Nuritasari (SAINTIS Publishing, 2022)
This study aims to describe the students' thinking ability in solving mathematical problems with Islamic nuances on the subject of the 7th grade set of MTs Darul Ulum Banyuanyar. Before conducting the research, the subject was given learning or knowledge about mathematics with Islamic nuances, more specifically the set material. The technique of taking research subjects is done by using purposive sampling technique. The selected subjects were 3 respondents. In checking the validity of the research using triangulation, the triangulation used is time triangulation. The results of this study indicate that high-ability students can pass all indicators in the indicators of critical thinking, creative and inductive reasoning. Meanwhile, for students with moderate abilities (second and third subjects) in critical thinking, the two subjects go through elementary clarification indicators, not through basic support indicators and determine strategies and tactic. Indicators for drawing conclusions (inference) and further clarification (advances clarification) can be passed, but in the work carried out, it is not done correctly. In creative thinking, students with moderate ability are both through the indicators of fluency and flexibility, and not through indicators of originality and elaboration. Whereas in inductive reasoning the second subject only met two of the 3 indicators of inductive reasoning, namely, fulfilling the indicators of identifying mathematical processes/concepts and their tendencies from the given situation, and compiling estimates relevant to the statement. Meanwhile, in inductive reasoning, the third subject only fulfills one indicator, namely identifying mathematical processes/concepts and their tendencies from the given situation.